Research on the Influence Law of Water Level in Outer Rivers and Rainfall Peak Position Coefficients on Typical Urban Waterlogging - LIN Geng; XU Yixi; SONG Lixiang (Renmin Zhujiang)
Water level in outer rivers and rainfall peak position coefficients are important factors affecting the severity of urban waterlogging.Therefore,exploring their influence law is of great significance for mechanism analysis and prevention of waterlogging.In this study,a typical urban area was taken as an example to establish the urban waterlogging model coupled with a pipe network,river channel,and surface.Then,the model was used to calculate the waterlogging risk of the area under six situations derived from two conditions of outer river water level and three conditions of rainfall peak position coefficients.Then,the influence of outer river water level and rainfall peak position coefficients on urban waterlogging was quantitatively analyzed.On this basis,corresponding strategies to alleviate urban waterlogging were proposed.The results show that the water level in outer rivers has a significant effect on flat urban areas whose elevation is close to the water level in outer rivers.The higher risk level of waterlogging indicates a higher growth rate of inundated areas after the water level in the outer river increases.In the same rainfall intensity,the lower rainfall peak position coefficient indicates more serious waterlogging.Therefore,comprehensive upstream and downstream measures should be taken from the holistic view of watersheds to effectively reduce waterlogging disasters.This study provides ideas and references for understanding the law of urban waterlogging and coping with waterlogging.